Predictors of job satisfaction and organizational commitment of special education teachers - Garcia, Bernadette Del Prado (2007)
The cumulative effect of SPED teachers leaving the country is a massive drain in society. For this reason, it becomes imperative to gather data on the factors that influence job satisfaction with the assumption that a satisfied employee remains in an organization. A descriptive correlational method of research employing a quantitative design was conducted using a 3-part self-administered questionnaire. Forty-six elementary teachers from 20 public schools from Quezon City served as respondents. Results showed that salary and responsibility and work itself are the most significant predictors of job satisfaction of SPED teachers. A strong linear positive relationship exists between job satisfaction and organizational commitment, which lends support to existing literature and related studies.